IMPLEMENTASI KEBIJAKAN PEMERINTAHAN DESA TULUNGREJO DALAM MEMBANGUN EDUWISATA KAMPUNG INGGRIS PARE - Imsawati, Auny Vidiyan; Supardal, Supardal (Journal of Indonesian Rural and Regional Government, 2025)
Educational tourism (eduwisata) is a combination of tourism and education, eduwisata is a positive tourism concept that combines the two fields with learning and tourism. Eduwisata is a non-formal learning activity that is not rigid in its learning activities. Kediri Regency Regional Regulation Number 2 of 2020 concerning the Master Plan for Tourism Development in Kediri Regency for 2019-2034 which is stated in Attachment II of Kediri Regency Regional Regulation Number 2 of 2020 has been stipulated on September 2, 2020 concerning the regional map for the development of Regency Tourism Destinations as a geographical area in Kediri Regency. This study will examine the implementation of the Tulungrejo village government policy in developing eduwisata in Kampung Inggris, Pare, Kediri, East Java based on the seven sapta pesona: safe, orderly, clean, cool, beautiful, friendly, and memorable. This study uses qualitative methods by conducting interviews and Focus Group Discussions (FGD). The results of this study indicate that the policy implementation between the Tulungrejo village government and the Kampung Bahasa Forum, which comprises community members, is not yet effective and requires optimization. The Kampung Inggris (English Village Forum) should prioritize and prioritize the interests of Kampung Inggris residents in developing educational tourism.